Application of optimal homotopy asymptotic method for the approximate solution of riccati equation - Fazle Mabood,; Ahmad Izani bin Md Ismail,; Ishak Hashim, (Universiti Kebangsaan Malaysia, 2013)
In this paper, the optimal homotopy asymptotic method (OHAM) is applied to obtain an approximate solution of the nonlinear Riccati differential equation. The method is tested on several types of Riccati differential equations and comparisons that were made with numerical results showed the effectiveness and accuracy of this method.